Association and Incident Rate of Nosocomial Infections with Low Birth Weight in Public vs. Private Sector Deliveries - Sharmeen Ilyas; Saleem Adil; Madeeha Rashid; Muhammad Ali Zahid; Aisha Qaiser; Atif Munir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Nosocomial infections (NIs) are a major contributor to neonatal morbidity and mortality in low- and middle-income countries. Low birth weight (LBW) infants are particularly vulnerable due to compromised immunity, increased invasive interventions, and prolonged hospitalization. In Pakistan’s Lahore Punjab, where healthcare systems face urban–rural disparities, the comparative burden of NIs in LBW neonates across public and private sector deliveries remains insufficiently explored. Aims & Objective: This study aimed to evaluate the association between LBW and nosocomial infections and to estimate the incidence rate of NIs among neonates delivered in public versus private sector hospitals in Lahore Punjab, Pakistan. Methodology: A retrospective cohort study was conducted on 177 neonates admitted to neonatal intensive care units (NICUs) of two public and two private tertiary hospitals in Lahore Punjab from July to December 2023. Data were collected from medical records, including neonatal demographics, birth weight, delivery mode, maternal risk factors, length of stay, and confirmed NI episodes. Incidence rates were calculated per 1,000 patient-days. Logistic regression was applied to determine the association of LBW with NIs, adjusting for confounders such as prematurity, invasive device use, and maternal comorbidities. Results & Findings: Of the neonates studied, 46% (n=82) were LBW. The overall incidence rate of NIs among LBW infants was 28.6 per 1,000 patient-days, compared to 12.3 per 1,000 patient-days in normal birth weight neonates. LBW was significantly associated with NI development (adjusted odds ratio [aOR]: 3.14, 95% CI: 1.82–5.41, p<0.001). Public sector hospitals recorded a higher NI incidence (34.8 per 1,000 patient-days) compared to private hospitals (19.7 per 1,000 patient-days). Bloodstream infections (41%) and neonatal pneumonia (33%) were the most common NIs. Prolonged hospitalization (>10 days) and invasive device use (central lines, mechanical ventilation) were independent predictors of NI development (p<0.05). Rural-born neonates admitted to public sector facilities exhibited the highest NI rates. Conclusion: Low birth weight is strongly associated with an elevated risk of nosocomial infections in Lahore Punjab. The burden is disproportionately higher in public sector and rural-serving hospitals, reflecting systemic gaps in infection prevention, NICU infrastructure, and resource allocation.